FEATURES OF A DIFFERENTIAL DIAGNOSIS OF PEDIATRIC ACUTE MONOCYTIC LEUKEMIA (AML-M5a) ON THE EXAMPLE OF A CLINICAL CASE - O. I. Kit; N. K. Guskova; O. N. Selyutina; V. V. Dmitrieva; I. A. Novikova; I. S. Torpujyan; V. R. Zakharchenko (Южно-Российский онкологический журнал, 2020)
The aim of this work was to assess the significance of investigating clinical and laboratory parameters for diagnosing acute monocytic leukemia in children on the basis of a clinical case. The article demonstrates specific features of differentiating AML M5a from other forms of acute myeloid leukemia. According to the results of hematological, morphological and cytofluorimetric studies of blood and bone marrow samples, the diagnosis of acute myeloid leukemia was established. The morphological and phenotypic characteristics of blast cells hampered the diagnosis of an AML form. However, a comprehensive analysis of the expressed CD antigens allowed acute monocytic leukemia to be identified, which diagnosis was subsequently confirmed by a cytochemical study. Thus, the clinical diagnosis was established over a short period of time. This was of importance given the rising severity of the patient’s condition requiring immediate treatment, the initial hyperleukocytosis and the development of life-threatening complications associated with leukostasis in the lungs and the central nervous system. In the presented case, the clinical manifestations of the underlying disease and the results of flow cytofluorimetry were determining factors in initiating timely specific therapy.